Dynamism and Multifunctional Language Thesaurus Reflection (Linguostylistic Studies, 2015)
The problems of systematic study of the vocabulary of the Ukrainian language the end of XVIII - beginning of XXI centuries is discussed, which is reflected in the general linguistic thesaurus and the summary index of vocabulary of the Ukrainian language. Electronic thesaurus consists of twenty Ukrainian language dictionaries of different types and ages, so all-embracing reflects its structural and functional features.The dynamism of the language system is studied in the areas of highest tension caused by the formation of new words and meanings, communicative interaction spheres, loan words, variability of language means etc. The dynamics of the lexical structure of language reflects headings lexicographic parameters and structural-functional complex marks. Thesaurus is created as an open multi-functional system similar to the language system that reflects a holistic view of the world, which, according to M.V. Pimenova vision, realized as the sum of the theoretical (philosophical and scientific), non-theoretical (religious and art) and pre-scientific forms of knowledge. Thesaurus reflects the basic functions of the language, so is the prospect for new Lexicography thesauruses and dictionaries, including of ideographic type. Key words: Thesaurus, Dictionary synthesis, polyfunctionality of language, the dynamism of the language system, variants of words, loan words, figurative words, terms. References